CASE OF TREATMENT OF A PANCREATODUODENAL ARTERY ANEURYSM COMPLICATED BY RECURRENT GASTROINTESTINAL BLEEDING - Замятин, Вадим Анатольевич; Мугатасимов, Игорь Григорьевич; Верещагин, Максим Алексеевич; Андрейчук, Дмитрий Владимирович; Халепа, Владимир Иванович (Medicine in Kuzbass, 2019)
We present a rare case of successful diagnostic and treatment of a pancreatoduodenal artery aneurysm, complicated by recurrent gastrointestinal bleeding in a 57 years old patient, using of an angiography and endovascular embolization in our clinic.
Keywords: pancreatoduodenal artery aneurysm; gastro-intestinal bleeding; endovascular surgery; embolization